Work environment and job satisfaction among teachers at a public and a private university - Alegre Morales, Ana (2017)
The objective of this study was to analyze the relationship between working environment and job satisfaction in teaching at a public university and one private. The sample was 62 teachers at the University Federico Villarreal and 38 teachers of the University Champagnat, who were assessment with the Working Environment Questionnaire and Job Satisfaction Questionnaire S20/23. It was found that teachers in private institutions have better working environment than public institution (p = .000) and also have higher job satisfaction (p = .000). In addition, the results indicated that there is a significant relationship between both variables only in private institution (p = .003).